As diretrizes das políticas neoliberais e suas consequências para a economia baiana (2011-2018) - Santos, Bruna Maria Dias dos (2021)
This dissertation has the general objective of evaluating the social and economic consequences arising from the use of neoliberal policies for the bahian economy in the period 2011 - 2018. Specifically, the work seeks to answer the following problem: the neoliberal policies established in the Brazilian economy, between the years of 2011 to 2018, brought socioeconomic benefits to the State of Bahia and its population? Therefore, the research developed, considering its general objective, will be carried out using the deductive method. Thus, initially, there is a rescue of the theoretical contributions of authors who discuss the impacts of neoliberal policies on central and developing economies, so that the reader can understand the dynamics of these policies and their impacts at national and state level. Subsequently, the analysis of the behavior of some macroeconomic variables - product, employment and public spending - was used, so that it was possible to investigate budget structures and levels of public investment for the State of Bahia. The general hypothesis defended here is that, the effective implementation of neoliberal policies, in the studied period, not only produced disastrous economic results (increase in income concentration; decrease or even fall in GDP; increase in unemployment and decrease in income, etc.) , but it also weakened the role of macroeconomic instruments to boost aggregate demand.